Effects of vaccination and interventions on nasal microbiome and BRD-associated pathogens in calves - Liu, Guoxing; Zhang, Sen; Xiang, Zhijie; Shirani, Ihsanullah; Chen, Yingyu; Guo, Aizhen (Frontiers in Microbiology, 2024)
Vaccination is a widely adopted measure to prevent diseases, but the process of immunization can induce a substantial stress response. This study aimed to investigate the impact of a combined Mycoplasma bovis-BoHV-1 vaccine on the upper respiratory tract microbiome and BRD-associated pathogens in calves, as well as to evaluate the effects of potential interventions. The results showed that the percentage of Pasteurella species in the upper respiratory tract was elevated in calves after vaccination without intervention, and Pasteurella multocida was activated and proliferated. Interestingly, none of the three interventions (Sodium selenite-vitamin E, Astragalus polysaccharide and Ceftiofur sodium) affected antibody production after immunization. The administration of sodium selenite-vitamin E and astragalus polysaccharide reduced serum levels of cortisol and malondialdehyde, increased glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD), and alleviated the proliferation of Pasteurella multocida. Furthermore, the use of ceftiofur sodium almost completely inhibited the proliferation of Pasteurella multocida induced by immune stress. These findings provide a reference for mitigating the negative impacts associated with vaccination and highlight the potential benefits of using targeted nutritional and antimicrobial interventions to optimize immune responses and maintain a stable respiratory microbiome in calves.